2022
DOI: 10.15663/wje.v27i2.925
|View full text |Cite
|
Sign up to set email alerts
|

Navigating (mis)assumptions in exploring teachers’ knowledge and practice of multiliteracies pedagogy

Abstract: My research aims to explore teachers’ literacy experiences and teaching practices in New Zealand intermediate schools through the lens of multiliteracies pedagogy (MLP). However, upon the initial semi-structured interview, I realised my (mis)assumptions and learned that it could be demanding and challenging for teachers to narrate their literacy teaching beliefs and practices. Consequently, I reworked my interview protocols and switched from semi-structured to unstructured interviews. Then I conducted them in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the context of L2 teaching and learning, two important considerations emerge: (i) fostering inclusive classrooms that address student diversity in learning styles, preferences, interests and needs; and (ii) recognising the evolving nature of language and communication. From these perspectives, effective teaching and learning must actively engage students' prior knowledge, build on their strengths, and explicitly teach multimodality (Yap, 2023). Studies on first language settings have reported numerous benefits of MLP; however, investigations in L2 classrooms contend that an examination‐driven and outcome‐orientated pedagogical approach has rendered the framework less pertinent in such environments (Cope & Kalantzis, 2009).…”
Section: Multiliteracies Pedagogy: Towards Greater Inclusivitymentioning
confidence: 99%
“…In the context of L2 teaching and learning, two important considerations emerge: (i) fostering inclusive classrooms that address student diversity in learning styles, preferences, interests and needs; and (ii) recognising the evolving nature of language and communication. From these perspectives, effective teaching and learning must actively engage students' prior knowledge, build on their strengths, and explicitly teach multimodality (Yap, 2023). Studies on first language settings have reported numerous benefits of MLP; however, investigations in L2 classrooms contend that an examination‐driven and outcome‐orientated pedagogical approach has rendered the framework less pertinent in such environments (Cope & Kalantzis, 2009).…”
Section: Multiliteracies Pedagogy: Towards Greater Inclusivitymentioning
confidence: 99%